Overview of distinct 5-methylcytosine profiles of messenger RNA in normal and knock-down NSUN2 colorectal cancer cells - Lin, Yu; Zhao, Zhifang; Nie, Wenqiang; Huang, Manting; Cai, Jiazhong; Wang, Yadong; Wang, Hesong; Huang, Yongmei; Bai, Yang (Frontiers in Genetics, 2023)
Background: Colorectal cancer (CRC) is a harmful cancer with high morbidity and poor prognosis. There is growing evidence that RNA methylation is closely related to the occurrence of cancer and its malignant biological behavior. N6-methyladenosine (m6A) methylation is the most common RNA modification in eukaryotes, and its multiple regulatory mechanisms in CRC have been elucidated from multiple perspectives. At the same time, the role of 5-methylcytosine (m5C), another important and widely distributed methylation modification, in CRC is far from being elucidated. Methods: In this study, we used RNA immunoprecipitation sequencing combined with bioinformatics methods to identify the m5C peaks on messenger RNA (mRNA) in HCT15 cells and sh-NSUN2 HCT15 cells, understand which transcripts are modified by m5C, and characterize the distribution of m5C modifications. In addition, we performed further bioinformatics analysis of the detected data to initially clarify the potential function of these m5C-modified transcripts. Results: We found significant differences in the distribution of m5C between HCT15 cells and sh-NSUN2 HCT15 cells, suggesting that m5C is likely to play a key role in the occurrence and development of CRC. Furthermore, Gene Ontology (GO) enrichment analysis showed that genes altered by m5C were mainly enriched in phylogeny, synaptic membrane, and transcription factor binding. The Kyoto Encyclopedia of Genes and Genomes (KEGG)pathway analysis showed that the genes altered by m5C are enriched in ECM receptor interaction pathway, the circadian pathway, and the cAMP signaling pathway. Conclusion: Here, our study preliminarily revealed the different distribution patterns of m5C between HCT15 cell and sh-NSUN2 HCT15 cell. Our results open a new window to understand the role of m5C RNA methylation of mRNA in the development of CRC.